Pengaruh Kompetensi Dosen Terhadap Kinerja Dosen Di Universitas Sumatera Barat (Studi Kasus Pada Dosen Fakultas Ekonomi Universitas Sumatera Barat) - Sudirman (CV. ITTC INDONESIA, 2023)
This research aims to determine the Influence Of Lecturer Competency On Lecturer Performance At The University Of West Sumatra. The choice of this title is based on how much influence lecturers' competence has in improving lecturers' performance because we both know that lecturers are required to be able to update references and teaching patterns which involve students directly in order to realize the government's independent campus learning program. This research uses a quantitative type of research. The data taken was primary data by distributing questionnaires to lecturers majoring in management at the University of West Sumatra. This research carried out research instrument tests, classical assumption tests, hypothesis tests using SPSS version 21. The research results stated that looking at the results of the tests that had been carried out proved that lecturer competence had a significant effect on lecturer performance. and it can also be seen that the R Square is 0.601 or 60.1%. This means that 60.1% of lecturer performance variables are influenced by lecturer competence, the remaining 39.9% are influenced by other variables outside of the variables of this research.